Pesan Dakwah dalam Media Sosial TikTok Akun @kadamsidik00 - Fajrin , Muhammad (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
This research aims to analyze the forms of conveying da'wah messages found on one of the TikTok accounts which attracts many TikTok social media fans from young people, namely the @kadamsidik account. Apart from that, this research also aims to determine the response and impact of the da'wah message conveyed by @kadamsidik00 on social media viewers or netizens. The results of this research show that there are forms of conveying da'wah messages in general, namely Sharia, Akidah, and Akhlaq in TikTok content on the @kadamsidik00 account. The delivery of the da'wah message is accompanied by verses from the Qur'an so that the explanation is considered to be in accordance with the sources of Islamic teachings. Apart from that, this research shows various forms of netizen responses, both positive and negative. The implications of this research are able to create young preachers who are able to contribute to Islamic da'wah by taking advantage of opportunities on current social media